FaGAPC2/FaPKc2.2 and FaPEPCK reveal differential citric acid metabolism regulation in late development of strawberry fruit - Yang, Min; Hou, GouYan; Peng, YuTing; Wang, LiangXin; Liu, XiaoYang; Jiang, YuYan; He, CaiXia; She, MuSha; Zhao, ManTong; Chen, Qing; Li, Mengyao; Zhang, Yong; et al. (Frontiers in Plant Science, 2023)
Citric acid is the primary organic acid that affects the taste of strawberry fruit. Glycolysis supplies key substrates for the tricarboxylic acid cycle (TCA cycle). However, little is known about the regulatory mechanisms of glycolytic genes on citric acid metabolism in strawberry fruits. In this study, the citric acid content of strawberry fruit displayed a trend of rising and decreasing from the initial red stage to the full red stage and then dark red stage. Thus, a difference in citric acid metabolic regulation was suspected during strawberry fruit development. In addition, overexpression of either cytoplasm glyceraldehyde-3-phosphate dehydrogenase (FxaC_14g13400, namely FaGAPC2) or pyruvate kinase (FxaC_15g00080, namely FaPKc2.2) inhibited strawberry fruit ripening and the accumulation of citric acid, leading to a range of maturity stages from partial red to full red stage. The combined transcriptome and metabolome analysis revealed that overexpression of FaGAPC2 and FaPKc2.2 significantly suppressed the expression of phosphoenolpyruvate carboxykinase (FxaC_1g21491, namely FaPEPCK) but enhanced the content of glutamine and aspartic acid. Meanwhile, the activities of PEPCK and glutamate decarboxylase (GAD) were inhibited, but the activities of glutamine synthase (GS) were increased in FaGAPC2/FaPKc2.2-overexpressed fruit. Further, functional verification demonstrated that overexpression of FaPEPCK can promote strawberry fruit ripening, resulting in a range of maturity stage from full red to dark red stage, while the citric acid synthase (CS) activities and citric acid content were significantly decreased. Overall, this study revealed that FaGAPC2/FaPKc2.2 and FaPEPCK perform an important role in reducing citric acid content in strawberry fruit, and FaGAPC2/FaPKc2.2 mainly by promoting the GS degradation pathway and FaPEPCK mainly by inhibiting the CS synthesis pathway.